2003
DOI: 10.1098/rspb.2003.2498
|View full text |Cite
|
Sign up to set email alerts
|

Defective or effective? Mutualistic interactions between virus genotypes

Abstract: Defective viruses lack genes essential for survival but they can co-infect with complete virus genotypes and use gene products from the complete genotype for their replication and transmission. As such, they are detrimental to the fitness of complete genotypes. Here, we describe a mutualistic interaction between genotypes of an insect baculovirus (nucleopolyhedrovirus of Spodoptera frugiperda (Lepidoptera)) that increases the pathogenicity of the viral population. Mixtures of a complete genotype able to be tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
99
1
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 36 publications
5
99
1
5
Order By: Relevance
“…Even defective viruses, which often reduce the virulence of the virus population (e.g. Muñoz et al, 1998;Zwart et al, 2008), in some particular instances increase the virulence of the population when co-infecting with a helper virus (Lopez-Ferber et al, 2003;Lauzon et al, 2005). Here, however, we have identified a case were genetic heterogeneity is inversely correlated with disease outbreaks.…”
contrasting
confidence: 45%
“…Even defective viruses, which often reduce the virulence of the virus population (e.g. Muñoz et al, 1998;Zwart et al, 2008), in some particular instances increase the virulence of the population when co-infecting with a helper virus (Lopez-Ferber et al, 2003;Lauzon et al, 2005). Here, however, we have identified a case were genetic heterogeneity is inversely correlated with disease outbreaks.…”
contrasting
confidence: 45%
“…One proposal is that genome segmentation evolved in response to high mutation rates to provide multicomponent reproduction as a form of sex to attenuate the effect of deleterious mutations (5,31). In this respect, it has been recently reported that genomes of nucleopolyhedrovirus with deletions can work with full-length partners to mutual benefit, possibly through complementation (19). Another proposal is that segmentation could result from selection of shorter RNA molecules that replicate faster than the corresponding parental genome, favored at high MOIs to ensure efficient complementation (25,40).…”
Section: Discussionmentioning
confidence: 99%
“…However, pif1-and pif2-defective genotypes can replicate autonomously in cell culture or in larvae, if injected. Remarkably, the progeny viruses from insects that had been simultaneously inoculated with a mixture of complete and deletion genotypes, in a ratio similar to that found in nature (ϳ3:1), were ϳ2.5 times more pathogenic, as indicated by concentration-mortality metrics, than the complete genotype alone (28,38,39). Whether the increased pathogenicity of mixed genotype inocula was specifically due to the deletion has remained unclear and identifying the gene(s) involved represents a key to our understanding of baculovirus infection strategies.…”
mentioning
confidence: 95%
“…Primers were designed to differentiate between genotype SfNIC-B (amplicon of ϳ750 bp) and the recombinant genotypes SfNIC-B⌬16K (amplicon of 1,076 bp) and SfNIC-B⌬pifs (amplicon of 868 bp) (B-pif2fw, Sfpif.4, and Sf100a; Table 1). Reactions were stopped at the mid-logarithmic phase of amplification (19 cycles), since a series of amplifications involving different numbers of cycles indicated that this was the mid-logarithmic phase for the amplification of this product, as described in previous studies (28,40,41). The intensities of PCR products were determined relative to the SfNIC-B internal standard by using the ChemiDoC densitometric analysis software (Bio-Rad, Hercules, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation